Pembuatan Bioetanol Tongkol Jagung (Zea mays) dan Batang Pisang (Musa paradisiaca) sebagai Bahan Bakar Alternatif - Putri Asyifa Nurohmah; Najwa Muhbita Alya; Nurul Hidayati; Susanti Rahayu (SMA Trensains Muhammadiyah Sragen, 2024)
The demand for fuel oil in Indonesia has sharply increased along with the population growth, while the reserves of these energy sources are becoming increasingly limited. Bioethanol, an alternative fuel processed from plants, has the advantage of reducing CO2 emissions by up to 18%. However, corn cob waste and banana tree stem waste in Indonesia have not been utilized properly, despite their high cellulose and hemicellulose content. The aim of this research is to produce bioethanol from corn cob and banana stem waste, creating a more environmentally friendly fuel source that reduces reliance on limited fossil fuels. The study employs a descriptive quantitative method focused on bioethanol production from the aforementioned waste materials. Data was collected through experimentation, observation, and literature review. The obtained data was analyzed using descriptive methods. The study conducted combustion tests and analyzed the water content of bioethanol. After conducting tests, it was found that the carbon dioxide content is lower than that of typical fuel. Additionally, the bioethanol contains 1.65% water content. This research successfully identified the effectiveness of bioethanol as a more environmentally friendly fuel oil source.